The Implementation of Talak Ba’in Sughro towards Apostate Husband - Ahmad Nafhani; Abdullah Arief Cholil (Law Development Journal, 2020)
The purpose of marriage is to form a happy and eternal family based on One Godhead. Marriage can be broken up because one party is Apostate, Apostasy can cause a problem in the household. In this study, the panel of judges decisions in accordance with the laws in Indonesia, namely Act No. 1 of 1974 and Compilation of Islamic Law. The method used by juridical normative focuses on the inventory of positive law, legal principles and doctrines, legal findings in concrete, legal systematics, level of legal synchronization, comparative law. Research findings the Demak Religious Court based on its relative and absolute competence has the right to examine, decide, and settle the case at the first level, so it is appropriate if the Plaintiff registers the case with the Demak Religious Court, for divorce on grounds, religious conversion or apostasy which causes dissonance in the household . That the separation that occurred as a result of the apostasy of one of the husband and wife couples from Islam was a fasakh, not a fall in the divorce of Ba’in Sughro. The purpose of the research itself is to be able to present accurate data so that it can provide benefits and be able to solve problems.